2014
DOI: 10.1159/000364823
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Neck Circumference and Its Correlation with Body Composition in a Sample of Students in São Paulo, Brazil

Abstract: Purpose: The purpose of this study was to verify the correlation between neck circumference (NC) and body mass index (BMI) in children, and to determine NC percentiles for Brazilian children. Methods: The subjects of this cross-sectional study were students between the ages of 6 and 19 years from five schools in São Paulo, Brazil. Clinical and anthropometric data were collected from the students from April 2011 to June 2012. NC was measured at the level of the cricoid cartilage. We calculated Pearson correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 32 publications
3
30
2
1
Order By: Relevance
“…The results of this study have shown that body weight and BMI have a positive correlation with NC, corroborating other studies conducted with children older than 2 years of age, in Brazil and other countries. 7,9,12,13,[15][16][17][18]20 The results of the present study also show that there was a moderate positive correlation between NC and BMI in both genders according to age group, supporting the results from studies conducted with Turkish, American and Chinese children. 7,12,18 However, some important limitations should be considered.…”
Section: Neck Circumference To Identify Excess Body Weight In Childresupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study have shown that body weight and BMI have a positive correlation with NC, corroborating other studies conducted with children older than 2 years of age, in Brazil and other countries. 7,9,12,13,[15][16][17][18]20 The results of the present study also show that there was a moderate positive correlation between NC and BMI in both genders according to age group, supporting the results from studies conducted with Turkish, American and Chinese children. 7,12,18 However, some important limitations should be considered.…”
Section: Neck Circumference To Identify Excess Body Weight In Childresupporting
confidence: 88%
“…17 Until the publication of this study, only NC measures with children five years of age or over had been reported. 7,9,12,13,[15][16][17][18][19][20][21] This study has several strengths. It is a homebased design, which includes primary data from a non-institutionalized population.…”
Section: Neck Circumference To Identify Excess Body Weight In Childrementioning
confidence: 99%
See 1 more Smart Citation
“…NC and the technical aspects to measuring it Seventy-two percent (72%) of the studies performed measurements at the level of the thyroid cartilage, an easily identifiable reference landmark. The other measurement sites were: just below the thyroid cartilage, 23 the cricoid cartilage 8,30 and at halfway the height of the neck. 21,26 In only three studies the measurements had been taken as duplicates or triplicates, 15,23,25 a fact of little relevance due to the already well-documented reproducibility of this type of measurement.…”
Section: Characterization Of Studiesmentioning
confidence: 99%
“…The reference population data was previously described (6), and presented in this study including 3,651 school students from five government and private schools and family members (Male: 1,838; Female: 1,813), height SDS (mean ± SD) of 0.33 ± 1.1 and 0.21 ± 0.93 was observed in female and male controls, respectively. Height and target height were grouped by chronological age from 2 to 18 years, and ≥ 19 years in boys, and from 2 to 15 years, and ≥ 16 years in girls (Table 1).…”
Section: Control Population Groupmentioning
confidence: 99%